Insect pollinator diversity along a habitat quality gradient on Mount Slamet, Central Java, Indonesia - IMAM WIDHIONO; EMING SUDIANA; EDY TRI SUCIANTO (Biodiversitas Journal of Biological Diversity, 2016)
Widhiono I, Sudiana E, Sucianto ET. 2016. Insect pollinator diversity along a habitat quality gradient on Mount Slamet,Central Java, Indonesia. Biodiversitas 17: 746-752. The diversity of wild bees and wasps in seven habitat types (natural forest, teak forest, pine forest, Agathis forest, community forest, gardens, and agricultural areas) representing the habitat quality gradient of Mount Slamet and adjacent areas in Central Java, Indonesia, was studied from April to June 2012. We examined whether habitat quality affected the diversity of wild bees and wasp pollinators. In total, 938 wild bee and wasp specimens representing 13 species of bees and 2 species of wasps were collected using kite netting. Wild bee diversity differed significantly among the habitat types (F 6,281 = 1.2 p < 0.05). The Spearman’s correlation coefficients confirmed that wild bee diversity was correlated with habitat quality (r2 = 0.67 p < 0.05).Habitats that included all of the major wild plant species supported the highest wild bee diversity.